Explaining the food safety behaviours of food handlers using theories of behaviour change: a systematic review. Issue 3 (4th May 2018) - Young, Ian; Thaivalappil, Abhinand; Greig, Judy; Meldrum, Richard; Waddell, Lisa
ABSTRACT: Theories of behaviour change can explain the factors affecting food handlers' use of food safety practices. A systematic review was conducted on this topic to identify which theories have been applied in this area and to determine which theories are the most consistent predictors of food handlers' behaviours. Standard systematic review procedures were followed: comprehensive search strategy; relevance screening of abstracts; article characterization; data extraction; risk-of-bias assessment; and descriptive analysis. Among 19 relevant studies, the most commonly investigated theories were the Theory of Planned Behaviour ( n  = 9 studies) and Health Belief Model ( n  = 5). All investigated theories were useful to explain food handlers' behavioural intentions and behaviours related to food safety across different settings, and could serve as useful frameworks for future research and practice. However, there was wide variability in the predictive ability of the theories and their specific constructs, indicating theories should be adapted to the local context of application.